A tale of three distributions: Inheritances, wealth and lifetime income - Rowena Crawford; Andrew Hood (Institute for Fiscal Studies (IFS), 2015)
This paper investigates the impact of inheritances and gifts received on the distribution of wealth among older households in England, and the implications for inequality in lifetime incomes. Whereas previous work has looked only at marketable wealth, we consider broader measures including public and private pensions. We find that once pension wealth is included, inheritances and gifts no longer have an equalising impact on the distribution of wealth. Without pension wealth, including transfers takes the wealth share of the top 10% from 40% to 38%; with pension wealth, the impact is near zero. This has important implications for the impact of inheritances and gifts on the distribution of lifetime incomes. Exploiting a link with administrative data on lifetime earnings, we show that savings rates are significantly increasing in lifetime incomes when pension wealth is excluded, but less so when it is included. Our results thus indicate that the impact of intergenerational transfers on the distribution of lifetime incomes among these individuals is likely to be negligible or inequality-increasing, rather than inequality-reducing.
Keywords: 330